Improving the echocardiographic assessment of pulmonary pressure using the tricuspid regurgitant signal—The "chin" vs the "beard". Issue 8 (20th April 2018) - Kyranis, Stephen J.; Latona, Jilani; Platts, David; Kelly, Natalie; Savage, Michael; Brown, Martin; Hamilton‐Craig, Christian; Scalia, Gregory M.; Burstow, Darryl
Abstract : Aim: Transthoracic echocardiography (TTE) is a fundamental investigation for the noninvasive assessment of pulmonary hemodynamics and right heart function. The aim of this study was to assess the correlation and agreement of Doppler calculation of right ventricular systolic pressure (RVSP) and pulmonary vascular resistance (PVR) using "chin" and "beard" measurements of tricuspid regurgitant velocity (TRVmax ), with invasive pulmonary artery systolic pressure (PASP) and PVR. Methods: One hundred patients undergoing right heart catheterisation (RHC) and near simultaneous transthoracic echocardiography were studied. TRVmax was recorded for "chin" measurement (distinct peak TRVmax signal) and where available (63 patients), "beard" measurement (higher indistinct peak TRVmax signal). Results: Measurable TRV signal was obtained in 96 patients. Mean RVSPchin 54.7 ± 22.7 mm Hg and RVSPbeard 68.6 = 23 ± 26.3 mm Hg ( P  < .001). There was strong correlation between both RVSPchin and RVSPbeard with invasive PASP (Pearson's r  = .9, R 2  = 0.82, P  < .001 ‐ r  = .88, R  = .78, P  < .001, respectively.). Bland‐Altman analysis for RVSPchin and RVSPbeard showed a mean bias of −0.5 mm Hg (95% limits of agreement −21.4 to 20.5 mm Hg) and −10.7 (95% LOA −35.5 to 14.2 mm Hg), respectively. Receiver operator characteristics of TRVmax "chin" and "beard" for diagnosis of pulmonary hypertension was assessed with optimal cut‐offs being 2.8 m/s (sensitivity 93%, specificity 87%) and 3.2 m/s (sensitivity 91%, specificity 82%), respectively. There was similar correlation between PVRchin and PVRbeard ( r  = .87, R 2  = 0.75, P  < .001 and r  = .86, R 2  = 0.74, P  < .001, respectively). At higher PVR, there was overestimation of calculated PVR using PVRbeard . Conclusion: The accuracy of noninvasive measurement of right heart pressures is increased using the "chin" in estimation of both RVSP and PVR.